(3OSJhQ (B:s (3GJMGO GdLeghQjGJ GdGTJQGcjI GdShajjJjI (B-(3GdbGffhf GdGSGSj (B/s - (3GdShajjJ GdCYdis ((3ehSch (B:s (3GdEJMGO GdShajjjJj ,s, 1977)
(3GbQg GdShajjJ GdGYdi aj GdGJMGO GdShajjJj aj OhQJg GdSGHYI GdGSJKfGFjI ef GdMdbI GdJTQjYjI GdJGSYI (B7 (3JTQjf GdGhd (B((3GcJhHQ(B1977s